The prevalence of gallstone disease after sleeve gastrectomy and Roux en Y gastric bypass - Mukhtar, Ramiz S.; Saloom, Adil K.; AbdulJabbar, Mohammed Q. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Obesity (body mass index >30) is increasing worldwide with an estimated 1.7 billion people currently affected by the disease, Gallstone represent the third most common disease observed among obese patients. Moreover about 30% of the patients who are candidates for bariatric surgery either have undergone a prior cholecystectomy or are found to present gallstones at time of surgery, On the other hand, newly formed gallstones may be diagnosed in 27% to 43% of patients who have undergone bariatric surgery within a very short period of time. Objective: To determine the prevalence of gallstone disease requiring cholecystectomy after laparoscopic sleeve gastrectomy and roux en Y gastric bypass during a one year follow up and to determine the need for prophylactic cholecystectomy in these patients. Patients and methods: prospective study among patients with morbid obesity treated with laparoscopic sleeve gastrectomy and Roux- en- Y Gastric Bypass between 1st of February 2013 till 31st of July 2015 at Saint Raphael hospital and Al-Hayat private hospital, patients with negative abdominal ultrasound preoperatively, patient with at least one year follow up after surgery were included in this study, The patients were divided into two groups for comparison. Group A patients who had laparoscopic sleeve gastrectomy, and group B included the patients who underwent laparoscopic Roux en Y gastric bypass. The primary outcome measure was the formation of symptomatic gallstones or sludge with or without complications. Results: 284 patients in group A(sleeve) and 45 patients in group B(Bypass) were included in the analysis, the mean age of was 34.5 years for group A, and 191(67.3%) of the patients were women, whereas it was 41.5 years for group B and 33 (73.3%) of the patients were women, Symptomatic cholelithiasis subsequently requiring cholecystectomy occurred in 29 (10.2%) of 284 laparoscopic sleeve gastrectomy patients, and 5(11.1%) of 45 Roux en Y gastric bypass patients , symptomatic gallstone developed in a median of 7 months in group A, while the median time to developed symptomatic gallstone in group B was 8 months. No significant difference in symptomatic gallstone disease was found between the patients who underwent laparoscopic gastric bypass and those who had sleeve gastrectomy Conclusions: Cholelithiasis was common in our patients before weight reduction surgery. The rate for symptomatic gallstones after surgery was not so high.. Routine prophylactic cholecystectomy should not be recommended for these patients.